THE CONTRIBUTION OF GREEN ACCOUNTING, CORPORATE SOCIAL RESPONSIBILITY, AND GREEN INTELLECTUAL CAPITAL TO EARNINGS QUALITY - Wahyudi Widodo; Nofryanti; Holiawati (ZILLZELL MEDIA PRIMA, 2025)
This study aims to examine and analyze the contribution of green accounting, corporate social responsibility, and green intellectual capital to earnings quality in palm oil companies operating in Indonesia and Malaysia, by utilizing total assets and sales growth as control variables. This study is an associative quantitative study using secondary data. The data analysis method used in this research is panel data regression. The population in this study is all palm oil companies listed on the Indonesia Stock Exchange and Malaysia Stock Exchange within 2021-2023. The sample in this study was determined by applying a purposive sampling method, resulting in 23 research populations, which were then processed into 69 samples. The results show that green accounting, corporate social responsibility, and green intellectual capital simultaneously influence earnings quality. While green accounting has a positive effect on earnings quality, corporate social responsibility and green intellectual capital have no effect on earnings quality.